2012
DOI: 10.1590/s1806-66902012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da distribuição de sementes por uma semeadora de anel interno rotativo utilizando média móvel exponencial

Abstract: Resumo -Conceitos de qualidade cada vez mais se tornam essenciais para a sobrevivência da empresa agrícola, pois a importância do aprimoramento das operações agrícolas se faz necessária para a obtenção de resultados viáveis economicamente, ambientamente e socialmente. Uma das dimensões da qualidade é conseguir de conformidade, ou seja, a garantia de execução exata do que foi planejado para atender aos requisitos dos clientes em relação a um determinado produto ou serviço. Os objetivos deste trabalho são avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
2
8
0
11
Order By: Relevance
“…If the p-value (probability that the test statistic is extreme value regarding the observed value when the null hypothesis is true) for the Anderson-Darling test is lower than the level of significance, it is concluded that the data does not follow a normal distribution (ALBIERO et al, 2012).…”
Section: Aplication Of Normality Test To Datamentioning
confidence: 99%
“…If the p-value (probability that the test statistic is extreme value regarding the observed value when the null hypothesis is true) for the Anderson-Darling test is lower than the level of significance, it is concluded that the data does not follow a normal distribution (ALBIERO et al, 2012).…”
Section: Aplication Of Normality Test To Datamentioning
confidence: 99%
“…When compared to the results found by Zerbato et al (2014) in peanut crop and Albiero et al (2012) in the longitudinal distribution of seeds, the data were non-normal by the Anderson-Darling normality test. Zerbato et al (2014) report that the values of the kurtosis and asymmetry coefficients were greater than 0, and the asymmetry coefficient (Cs) showed positive asymmetric distribution (Cs> 0) and high asymmetry intensity (|Cs|> 1), while the kurtosis coefficient (Ck) had leptokurtic distribution with an elongated curve and with more agglomerated data.…”
Section: Descriptive Statistics On the Urea Distributionmentioning
confidence: 80%
“…The normality test indicated a normal distribution for the analyzed variables, even though this is not an assumption for the application of geostatistics. All variables presented values of asymmetry and kurtosis within the range of -2 and 2 (Table 3), which indicates that the data respect a normal distribution (Albiero et al, 2012;Melo et al, 2013;Silva et al, 2013).…”
Section: Layer (M)mentioning
confidence: 86%